1987
DOI: 10.1210/endo-120-4-1370
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Promoting Effects of Relaxin and Related Compositional Changes in the Uterus, Cervix, and Vagina of the Rat*

Abstract: Although the precise role of relaxin has yet to be elucidated, it has been implicated in the regulation of physiological and biochemical processes in the reproductive tract during pregnancy and parturition. In this study, the growth-promoting effects of relaxin and related compositional changes in the uterus, cervix, and vagina of immature ovariectomized estrogen-primed rats were examined. Relaxin increased the wet weight of the uterus, cervix, and vagina in a significant and linear manner over the log of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Alternatively, decidual IGF-BP has been shown to inhibit 1251I-IGF-I binding to both placental and endometrial receptors (46 The effects of relaxin on IGF-BP-I secretion have not been previously described. Extraluteal localization of relaxin to human endometrial stromal cells and decidual cells has been noted (49)(50)(51)(52), and the uterus is a major target tissue for relaxin effects on tissue growth and myometrial contractility (53)(54)(55)(56). The present observations suggest that relaxin may also be involved in the regulation of IGF-BP secretion by uterine tissues through autocrine or paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, decidual IGF-BP has been shown to inhibit 1251I-IGF-I binding to both placental and endometrial receptors (46 The effects of relaxin on IGF-BP-I secretion have not been previously described. Extraluteal localization of relaxin to human endometrial stromal cells and decidual cells has been noted (49)(50)(51)(52), and the uterus is a major target tissue for relaxin effects on tissue growth and myometrial contractility (53)(54)(55)(56). The present observations suggest that relaxin may also be involved in the regulation of IGF-BP secretion by uterine tissues through autocrine or paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Uterotrophic actions of relaxin, first described in the rat (Steinetz et al 1957), include both uterine water imbibition (Steinetz et al 1957, Zarrow & Brennan 1957 and increased uterine dry matter content associated with protein, collagen and glycogen accretion (Steinetz et al 1957, Vasilenko et al 1980, 1981, Vasilenko & Mead 1987. Early studies indicating that relaxin-rich extracts promoted endometrial growth in juvenile and ovariectomized rhesus monkeys (Hisaw & Hisaw 1964, Dallenbach-Hellweg & Hisaw 1966 were later confirmed by work involving the purified hormone (Goldsmith et al 2004), which showed that relaxin also stimulated endometrial angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is clear that some of these effects mimic those induced by estrogen. For example, like estradiol, relaxin increased expression of uterine insulin-like growth factor-I (Ohleth et al 1997, Kowalski et al 2004, gap junctions (Risek et al 1995, Lenhart et al 1999, vascular endothelial growth factor (Cullinan-Bove & Koos 1993, Unemori et al 1999, and uterine vascularization (Vasilenko & Mead 1987, Cullinan-Bove & Koos 1993. Estrogen receptors, which function classically as hormoneregulated transcription factors, can be activated both directly by estrogen and indirectly via crosstalk with peptide growth factor signaling pathways (Ignar-Trowbridge et al 1992, Ma et al 1994, Smith 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxin is involved in cervical dilatation (Downing & Sherwood, 1985), relaxation of the pubic symphysis (Steinetz et ai, 1960), inhibition of uterine contractility (Porter, 1971), and stimulation of uterine growth (Vasilenko & Mead, 1987). Intracervical administration of pig relaxin to primigravid beef heifers 4 or 5 days before expected parturition induced cervical dilatation and increased pelvic area Musah et ai, 1986a, b).…”
Section: Introductionmentioning
confidence: 99%